N-acetylcysteine inhibits TNF-a, sTNFR, and TGF-b1 release by alveolar macrophages in idiopathic pulmonary fibrosis in vitro - Cui, A.; Ye, Q.; ulrich.costabel@ruhrlandklinik.uk.essn.de, et al., R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: N-acetylcysteine (NAC) can act as an antioxidant. NAC slows the rate of decline of lung function in idiopathic pulmonary fibrosis (IPF) patients concurrently treated with prednisone and azathioprine. Objective: In this study we investigated the effect of NAC on the production of tumor necrosis factor (TNF)-a, interleukin (IL)-1b, IL-6, IL-8, IL-10, IL-12 (p70), IL-18, transforming growth factor (TGF)-b1, and the soluble TNF receptors (sTNFR1 and sTNFR2) by alveolar macrophages (AM) in IPF patients. Design: AMs were harvested by bronchoalveolar lavage (BAL) from 16 IPF patients and were cultured for 24 h with RPMI medium alone, or with lipopolysaccharide (LPS) (100 ng/ml), in the presence or absence of NAC at various concentrations. Results: NAC suppressed the production of TNF-a, its soluble receptors, and TGF-b1 by AMs in a dose-dependent manner. At the highest concentration of NAC (10 mM), the spontaneous or LPS-stimulated production of TNF-a, sTNFR1, sTNFR2, and TGF-b1 were significantly reduced. The LPSstimulated IL-1b production was also suppressed by 10 mM NAC. Conclusions: NAC has the potential to down-regulate the production of TNF-a and their soluble receptors, as well as TGF-b1 and LPS–stimulated IL-1b, by AM in IPF in vitro. NAC may have anti-inflammatory and anti-fibrotic effects.